Consideration of Discerationary Actions by the Police in the Application of Restorative Justice to the Resolution of Domestic Violence Cases (Study at the Directorate of General Criminal Investigation of the Lampung Regional Police) - Recca Ayu Hapsari; Nadira Tresya (Rechtsnormen: Journal of Law, 2024)
Background. Domestic violence (hereinafter abbreviated as domestic violence) is one form of violence that occurs in people's lives. The violence is often also referred to as dosmetic violence because it occurs in the domestic sphere, the problem of domestic violence is one of the important things that became a serious concern by the Indonesian government in the reform era. Purpose. How is the consideration of discretionary actions by the Police in the application of restorative justice to the resolution of domestic violence cases and how are efforts to overcome domestic violence crimes carried out by the Police? Method. The approach used in this study is a normative juridical approach and an empirical juridical approach to obtain correct and objective research results. Results. Consideration of Discretionary Action by the Police in the Application of Restorative Justice to the Resolution of Domestic Violence Cases is through a restorative justice approach.  Efforts to overcome domestic violence crimes carried out by the police are carried out through several stages, namely pre-emptive, preventive, repressive containment efforts. Conclusion. Consideration of Discretionary Actions by the Police in the Application of Restorative Justice to the Resolution of Domestic Violence Cases is through a restorative justice approach in accordance with procedures to provide legal certainty for victims based on restorative justice requirements in solving domestic violence crimes and additional requirements based on the provisions of Article 3 and Article 5 of the National Police Regulation of the Republic of Indonesia Number 8 of 2021 concerning Restorative Justice Handling of Crimes.